1998
DOI: 10.1063/1.120783
|View full text |Cite
|
Sign up to set email alerts
|

Electron-irradiation-induced deep level in n-type GaN

Abstract: Deep-level transient spectroscopy measurements of n-type GaN epitaxial layers irradiated with 1-MeV electrons reveal an irradiation-induced electron trap at EC−0.18 eV. The production rate is approximately 0.2 cm−1, lower than the rate of 1 cm−1 found for the N vacancy by Hall-effect studies. The defect trap cannot be firmly identified at this time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
51
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 118 publications
(61 citation statements)
references
References 17 publications
10
51
0
Order By: Relevance
“…This trap is most likely associated with the N vacancy. 6,7 Interestingly, the energy of this trap is close to that found in an unirradiated, undoped, semi-insulating ͑SI͒ reactive molecular beam epitaxial ͑RMBE͒ layer by the thermally stimulated current ͑TSC͒ technique. 8 However, there are very few DLTS studies on any type of MBE-grown GaN, perhaps due to the difficulty of fabricating good Schottky barrier diodes ͑SBDs͒, with small leakage currents.…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…This trap is most likely associated with the N vacancy. 6,7 Interestingly, the energy of this trap is close to that found in an unirradiated, undoped, semi-insulating ͑SI͒ reactive molecular beam epitaxial ͑RMBE͒ layer by the thermally stimulated current ͑TSC͒ technique. 8 However, there are very few DLTS studies on any type of MBE-grown GaN, perhaps due to the difficulty of fabricating good Schottky barrier diodes ͑SBDs͒, with small leakage currents.…”
mentioning
confidence: 70%
“…In the Arrhenius plots, for comparative purposes, we also present the signatures for traps B, C, D, and E, which were obtained on MOCVD GaN SBDs irradiated by 1 ϫ10 15 cm Ϫ2 , 1-MeV electrons. 6 Three of the traps, i.e., B, C, and D, are preexisting in the material and not affected by the irradiation, while trap E is induced by the electron irradiation, with a production rate of at least 0.2 cm Ϫ1 , and is believed to be due to the N vacancy. By comparing the signatures of E 1 and E, we find that they have similar activation energies, but some difference in the capture cross section.…”
Section: T Mmentioning
confidence: 99%
“…5 Recently, a strong effort by several groups has been devoted to the study of irradiation-induced defects in GaN and related compounds. [6][7][8][9][10] Most of the results are still not fully understood, but some useful conclusions have already emerged. As an example, for 30 years the N vacancy V N has been considered to be the dominant donor in GaN, 11 but it has just recently been shown that this assumption is not true, 7 at least for the best, present-day material.…”
Section: On the Main Irradiation-induced Defect In Ganmentioning
confidence: 99%
“…According to a detailed study by Wosinski 7 of a dislocation-related electron trap ͑a line-defect͒ in plastically deformed n-type GaAs crystals, an increase in the slope of the n T versus ln(W f ) lines means an increase in the density of strain-related dislocations. Therefore, in our case, we believe that the plasma treatments do not cause any meaningful increase in dislocation density, even under an etching biasvoltage of Ϫ150 V. Trap D, with E T ϭ0.23-0.27 eV and n ϭ(1 -2)ϫ10 Ϫ15 cm 2 , has been observed in thin GaN layers by many groups, using various techniques, including hydride vapor phase epitaxy ͑HPVE͒, [8][9][10] MOCVD, [11][12][13] and MBE. 14,15 Three of these studies are consistent with the proposition that trap D is at least sometimes related to threading dislocations.…”
mentioning
confidence: 99%